Homologous Recombination Repair Testing Patterns and Outcomes in mCRPC by Alteration Status and Race - Bilen MA; Khilfeh I; Rossi C; Muser E; Morrison L; Hilts A; Diaz L; Lefebvre P; Pilon D; George DJ (Dove Medical Press, 2024)
Mehmet Asim Bilen,1 Ibrahim Khilfeh,2 Carmine Rossi,3 Erik Muser,2 Laura Morrison,3 Annalise Hilts,3 Lilian Diaz,3 Patrick Lefebvre,3 Dominic Pilon,3 Daniel J George4 1Department of Hematology and Medical Oncology, Emory University School of Medicine, Atlanta, GA, USA; 2Janssen Scientific Affairs, LLC, Horsham, PA, USA; 3Analysis Group, Inc., Montréal, QC, Canada; 4Department of Medicine, Duke University Cancer Center, Durham, NC, USACorrespondence: Carmine Rossi, Analysis Group, Inc., 1190 avenue des Canadiens-de-Montréal, Tour Deloitte, Suite 1500, Montréal, QC, H3B 0G7, Canada, Tel +1 514-871-4233, Email carmine.rossi@analysisgroup.comBackground: Alterations in DNA damage repair genes in advanced prostate cancer (PC) may impact responses to therapy and clinical outcomes. This study described homologous recombination repair (HRR) testing patterns and clinical outcomes among patients with metastatic castration-resistant prostate cancer (mCRPC) by HRR alteration status and race in the United States (US).Methods: Clinical data in the nationwide (US-based) Flatiron Health-Foundation Medicine, Inc. (FMI) Metastatic PC Clinico-Genomic Database were evaluated (01/01/2011- 12/31/2022). Patients initiating first-line (1L) mCRPC therapy on or after mCRPC diagnosis were included. Testing patterns, time-to-next treatment, overall survival (OS), and time-to-prostate specific antigen response were described.Results: Of the 1367 patients with mCRPC and at least one HRR panel test prior to or on the date of 1L mCRPC therapy initiation, 332 (24.3%) were HRR positive (White patients: n = 219 [66.0%]; Black patients: n = 37 [11.1%]) and 1035 (75.7%) were HRR negative (White patients: n = 702 [67.8%]; Black patients: n = 84 [8.1%]). The mean time between first positive test and 1L mCRPC therapy initiation date was 588 days (White patients: 589 days; Black patients: 639 days). Among HRR positive relative to negative patients, trends for faster progression (respective 12-month rate overall: 71.1% and 63.7%; White patients: 72.5% and 64.0%; Black patients: 65.4% and 56.4%), shorter OS (respective 24-month rate overall: 46.8% and 51.9%; White patients: 48.6% and 46.2%; Black patients: 52.8% and 54.1%), and decreased treatment response (respective 12-month rate overall: 24.3% and 37.9%; White patients: 24.5% and 35.2%; Black patients: 17.0% and 43.9%) were observed.Conclusion: Patients with mCRPC positive for HRR alterations tended to exhibit poorer treatment responses and clinical outcomes than those with a negative status. These findings highlight the importance of timely genetic testing in mCRPC, particularly among Black patients, and the need for improved 1L targeted therapies to address the unmet need in HRR positive mCRPC.Keywords: burden of illness, electronic health records, homologous recombination repair genes, metastatic castration-resistant prostate cancer, next-generation sequencing testing, precision therapy